Research on Electromagnetic Radiation Characteristics of Energetic Materials - Yuanbo Cui; Deren Kong; Jian Jiang; Shang Gao (Magnetochemistry, 2022)
During the explosion of energetic materials, electromagnetic interference is generated, which can affect the normal operation of surrounding electronic equipment. Therefore, an electromagnetic radiation measurement device based on a short-wave omnidirectional antenna and ultra-wideband omnidirectional antenna was designed to measure the electromagnetic radiation generated by the explosion of energetic materials of different masses, and the electromagnetic radiation characteristics were obtained through data processing. The results showed that the electromagnetic signal can still be collected hundreds of milliseconds after the explosive is detonated, and the electromagnetic radiation generated by the explosion is continuous and intermittent, which is a phenomenon that has not been found in this field at present. The mass of the energetic material had a significant effect on the time-domain characteristics of the electromagnetic radiation generated by the explosion: the higher the mass of the energetic material was, the shorter the delay response of the electromagnetic signal was, the longer the duration was, and the earlier the peak appeared. The frequency of electromagnetic radiation signals generated by the explosion of energetic materials was mainly concentrated below 100 MHz, and the energy was most concentrated in the frequency band of 0~50 MHz. The composition of energetic materials had the greatest influence on the spectral distribution, and the spectral distribution of electromagnetic radiation produced by the explosion of explosives with different compositions had obvious specificity. The electromagnetic radiation intensity generated by the explosion of energetic materials had a strong correlation with the distance from the explosion center, and it significantly decreased as the distance increased. The structure and detonation method of energetic materials changed the geometrical motion pattern during the explosion, resulting in the non-uniformity of electromagnetic radiation propagation.